EKSPERIMENTASI MODEL PEMBELAJARAN PROBING PROMPTING YANG DIDUKUNG METODE RESITASI TERHADAP HASIL BELAJAR PADA MATA PELAJARAN IPS DI MTS ABU DARRIN BOJONEGORO - Fradani, Ayis Crusma; Rosyida, Fathia; Khasanah, Siti Kiswatun (FKIP Unswagati, 2018)
This study aim to find out whether there is a difference in the use of probing prompting learning model that supported by recitation methods on the learning outcomes of eight grides students in social studies subjects at MTs Abu Darrin Dander Bojonegoro in the academic year 2017/2018 compared to confessional models or lectures. This research is a type of experimental research, since this study directly examines the influence among variables to test the cause and effect of variables by giving treatment of the experimental group or class. Based on the results of analysis, the average value of the experimental class is 76.56 and the average value of the control class is 68.48. From the activites between the experimental class and the control class also proved with probing prompting learning model supported by the student recitation method the experimental class more focused on learning that was 75% compared to the control class with the lecture learning model which only 45%. So it can be concluded that there was an effect of probing prompting learning models supported by recitation methods to the learning outcomes of VIII classes in social studies subjects at MTs Abu Darrin Dander Bojonegoro 2017/2018.Keywords: probing prompting learning model, recitation method, social studies, learning outcomesÂ